1995
DOI: 10.1111/j.1365-2958.1995.mmi_17010085.x
|View full text |Cite
|
Sign up to set email alerts
|

Long stretches of short tandem repeats are present in the largest replicons of the Archaea Haloferax mediterranei and Haloferax volcanii and could be involved in replicon partitioning

Abstract: We report the presence of long stretches of tandem repeats in the genome of the halophilic Archaea Haloferax mediterranei and Haloferax volcanii. A 30 bp sequence with dyad symmetry (including 5 bp inverted repeats) was repeated in tandem, interspersed with 33-39 bp unique sequences. This structure extends for long stretches--1.4 kb at one location in H. mediterranei chromosome and about 3 kb in the H. volcanii chromosome. The tandem repeats (designated TREPs) show a similar distribution in both organisms, app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(180 citation statements)
references
References 20 publications
(42 reference statements)
5
170
0
5
Order By: Relevance
“…In subsequent years similar CRISPR arrays were found in Mycobacterium tuberculosis 6 , Haloferax mediterranei 7 , Methanocaldococcus jannaschii 8 , Thermotoga maritima 9 and other bacteria and archaea. The accumulation of sequenced microbial genomes allowed genome-wide computational searches for CRISPRs (the first such analysis was carried out by Mojica et al in 2000 10 ), and the most recent computational analyses revealed that CRISPRs are found in ~40% of bacterial and ~90% of archaeal genomes sequenced to date 11,12 (Box 1).…”
Section: Brief History Of Crispr Researchmentioning
confidence: 64%
See 1 more Smart Citation
“…In subsequent years similar CRISPR arrays were found in Mycobacterium tuberculosis 6 , Haloferax mediterranei 7 , Methanocaldococcus jannaschii 8 , Thermotoga maritima 9 and other bacteria and archaea. The accumulation of sequenced microbial genomes allowed genome-wide computational searches for CRISPRs (the first such analysis was carried out by Mojica et al in 2000 10 ), and the most recent computational analyses revealed that CRISPRs are found in ~40% of bacterial and ~90% of archaeal genomes sequenced to date 11,12 (Box 1).…”
Section: Brief History Of Crispr Researchmentioning
confidence: 64%
“…Early in 1995 Mojica et al suggested that the repeats were involved in replicon partitioning, based on their observations that an increased copy number of the repeats in Haloferax volcanii resulted in altered replicon segregation 7 . This effect, however, was not reproduced in similar experiments carried out in M. tuberculosis 14 .…”
Section: Brief History Of Crispr Researchmentioning
confidence: 99%
“…volcanii (Mojica et al 1995;. It suggests the functional integrity of TRs and CRISPRs may contribute a significant role in the molecular process of their genomes as such.…”
Section: Discussionmentioning
confidence: 99%
“…In 1995, Mojica and colleagues noticed long segments of short repeats in Archaea Haloferax mediterranei and Haloferax volcanii [103]. And five years later, after a computational analysis of known microbial genomes, the group characterized the clustered repeated short elements they had seen, calling them Short Regularly Spaced Repeats (SRSRs) [104].…”
Section: Discovery Of Crispr-casmentioning
confidence: 99%